Still life with monkey - Weber, Katharine, 1955- (Paul Dry Books, 2018)
"Duncan Wheeler is a successful architect who savors the quotidian pleasures in life until a car accident leaves him severely paralyzed and haunted by the death of his young assistant. Now, Duncan isn't sure what there is left to live for, when every day has become a broken series of unsuccessful gestures. Duncan and his wife, Laura, find themselves in conflict as Duncan's will to live falters. Laura grows desperate to help him. An art conservator who has her own relationship to the repair of broken things, Laura brings home a highly trained helper monkey--a tufted capuchin named Ottoline--to assist Duncan with basic tasks. Duncan and Laura fall for this sweet, comical, Nutella-gobbling little creature, and Duncan's life appears to become more tolerable, fuller, and funnier. Yet the question persists: Is it enough? Katharine Weber is a masterful observer of humanity, and Still Life with Monkey, full of tenderness and melancholy, explores the conflict between the will to live and the desire to die"Amazon.com.